(untitled) (Revista Electrónica Calidad en la Educación Superior, 2018)
This research paper presents the results of the evaluation of the social impact of the Special Education undergraduate program, of the University of Antioquia’s Education Faculty, in the East and Southwest subregions of the Antioquia department (Colombia). The main objective was to evaluate the impact of the Program among the graduates and other audiences. The methodology was carried out under a qualitative design, in the evaluative research modality, Social Programs impact type of evaluation. The results of the research were structured under the following categories: Assessment of the quality of the Program, the role of the Special Educator, significant experiences and their impact, and location and working conditions of the graduates. Finally, it poses recommendations to various academic units of the University. Keywords: special education, evaluation, social impact, graduates, occupational performance, assessment.